Fetal inflammatory response syndrome (FIRS) and outcome of preterm neonates – a prospective analytical study. (1st February 2019) - Francis, Febi; Bhat, Vishnu; Mondal, Nivedita; Adhisivam, Bethou; Jacob, Sajini; Dorairajan, Gowri; Harish, B. N.
Abstract: Objectives: To estimate the incidence of fetal inflammatory response syndrome (FIRS) in preterm neonates and correlate it with immediate and one-year neurodevelopmental outcome. Materials and methods: This prospective observational analytical study, in preterm neonates with gestational age between 26 and 34 weeks was conducted from May 2014 to December 2015 in a tertiary care hospital in South India. FIRS was defined as the presence of either elevated levels of interleukin-6 (IL-6) in cord blood ≥11 pg/ml and/or the placental histopathology showing evidence of fetal inflammatory response. One hundred and twenty neonates were recruited. During delivery 2 ml cord blood for interleukin-6 and placenta were collected and stored appropriately. Based on presence/absence of FIRS (IL-6 in cord blood ≥11 pg/ml and or features of placental fetal inflammation), neonates were grouped into two groups. The neonatal and maternal characteristics between two groups were compared. The short-term outcome parameters during NICU stay and neurodevelopmental outcome at one year of corrected age was compared between groups. Results: Among the 120 infants studied, 19 expired. Out of 101 babies discharged, 87 were followed up till corrected 1 year of age. On examination of placenta and cord blood, 50 neonates had evidence of FIRS (41.6%). So there were 50 neonates in FIRS and 70 in NO-FIRS group. The mean gestational age, birth weight, and gender distribution were comparable between the two groups. Mortality [OR: 2.44 (CI: 1.14–5.26)] and early hypotension [OR: 2.13 (CI: 1.1–4.2)] were significantly higher in the FIRS group. The neurodevelopmental assessment at corrected age of 1 year showed that infants with FIRS had lower mean motor developmental quotient by developmental assessment scale for Indian infants (DASII) [87.6 ± 9.15 versus 93.07 ± 9.3, p  < .04]. Conclusions: FIRS has a significant role on survival and neurodevelopmental outcome of preterm infants.